Green Jobs - Olivier Deschenes (Institute for the Study of Labor (IZA), 2013)
In recent years the prospect of 'green jobs' or 'green growth' policies have become increasingly prominent, proposed to solve both the environmental challenges associated with global climate change and the persistent unemployment problems observed in many industrialized countries. This short article begins by describing the conceptual, definitional, and measurement issues related to green jobs. I then review the existing evidence from the primarily simulation-based studies that attempt to assess the impact of green policies on employment. I draw two main conclusions from this exercise. First, my descriptive analysis of the U.S. Bureau of Labor Statistics data on green jobs highlights that green jobs currently represent a small share of overall employment in the U.S, and one that has seen relatively weak growth in the last decade. Second, due to the sizable heterogeneity in the scope and assumptions made in the existing simulation studies of the labor market impacts of green policies, it is difficult to make a definitive conclusion about their likely impact. More careful and detailed empirical research is needed to assess the job creation potential of green job policies.
Keywords: J08; J23; Q48; 330; green jobs; green growth; employment; labor markets; Umweltschutz; Beschäftigungseffekt; Umweltwirtschaft; USA